Dimensions of irish students religiosity - Inglis, TF (Economic & Social Studies, 1980)
This paper attempts to identify the dimensions of religiosity for Catholic university students in Ireland through survey data obtained in 1976. Glock and Stark's (1965 and 1968) dimensions of religiosity are reformulated for use in the Irish context. The suggested existence of a legalistic dimension to religiosity within a one-denominational society like Ireland is indicated through a factor analysis of the data. This legalistic dimension, although only prevalent among a minority of the students, is characterised by a rigid adherence to the institutional Church's rules and regulations. It is concluded that religiosity among the majority of Catholic university students in Ireland is primarily a less than daily supernatural faith which acts as the basis for a social consensus of values. However, except for a minority (approximately one-third) commitment to the institutional Church rarely extended beyond adherence to major Christian teachings and religious practices.
Keywords: Economics; Sociology